2020
DOI: 10.1136/bmjopen-2020-038531
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Cervical Cancer Prevention in Tanzania (CONCEPT) study: Cohort profile

Bariki Mchome,
Patricia Swai,
Chunsen Wu
et al.

Abstract: PurposeCervical cancer is a major cause of death among women in Eastern Africa, and the distribution of human papillomavirus (HPV) according to HIV status is inadequately characterised in this region. In order to guide future cervical cancer preventive strategies that involve HPV testing, the Comprehensive Cervical Cancer Prevention in Tanzania (CONCEPT) study was established in 2015. The CONCEPT cohort aims to investigate the natural history of HPV and determine acquisition and persistence patterns of high-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…In Tanzania, very limited studies estimating the coverage of cervical cancer screening by age exist [ 12 ]. However, a follow-up study that enrolled women aged between 25 and 60 years from three cervical cancer screening clinics from urban and semi-rural areas in Tanzania reported 17.2% (696/4,043) and 14.2% (438/3,074) of the women aged between 25 and 60 years had high-risk HPV (hr-HPV) at baseline and in the first follow-up, respectively [ 13 ]. Only 3.4% (139/4,043) of the women aged between 25 and 60 years had high-grade squamous intraepithelial lesion (HSIL) in the same study [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Tanzania, very limited studies estimating the coverage of cervical cancer screening by age exist [ 12 ]. However, a follow-up study that enrolled women aged between 25 and 60 years from three cervical cancer screening clinics from urban and semi-rural areas in Tanzania reported 17.2% (696/4,043) and 14.2% (438/3,074) of the women aged between 25 and 60 years had high-risk HPV (hr-HPV) at baseline and in the first follow-up, respectively [ 13 ]. Only 3.4% (139/4,043) of the women aged between 25 and 60 years had high-grade squamous intraepithelial lesion (HSIL) in the same study [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, a follow-up study that enrolled women aged between 25 and 60 years from three cervical cancer screening clinics from urban and semi-rural areas in Tanzania reported 17.2% (696/4,043) and 14.2% (438/3,074) of the women aged between 25 and 60 years had high-risk HPV (hr-HPV) at baseline and in the first follow-up, respectively [ 13 ]. Only 3.4% (139/4,043) of the women aged between 25 and 60 years had high-grade squamous intraepithelial lesion (HSIL) in the same study [ 13 ]. Another study by Dartell et al [ 11 ] reported lower sensitivity of VIA than HPV-testing in detecting HSIL cervical lesions during a hospital-based cervical cancer screening event in Dar es Salaam, Tanzania.…”
Section: Introductionmentioning
confidence: 99%
“…2 To determine whether there are, in fact, different rates of clearance by population, it will be necessary to analyze prospective data from settings that are underrepresented in the literature. We and others are analyzing data from the African Collaborative Center for Microbiome and Genomics Research (ACCME) 41 and CONCEPT (Tanzania) 44 cohorts. HPV clearance rates that differ by geographical region would have implications for microsimulation models of HPV natural history used for costeffectiveness analysis, which to date rely on transition probabilities from populations with steadily declining age-specific HPV prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…This study is part of the Comprehensive Cervical Cancer Prevention in Tanzania (CONCEPT) study. A detailed description of the cohort profile has been published elsewhere [ 11 ]. Data were collected between August 2015 and October 2018 at two cervical cancer screening clinics in the Kilimanjaro Region; Mawenzi Regional Hospital and Kilimanjaro Christian Medical Centre (KCMC), and one screening clinic in the Dar es Salaam Region; Ocean Road Cancer Institute (ORCI).…”
Section: Methodsmentioning
confidence: 99%